2003
DOI: 10.1108/14630010310812163
|View full text |Cite
|
Sign up to set email alerts
|

Interaction, identity and collocation: What value is a corporate campus?

Abstract: Corporate campuses have been justified on many grounds, including lower operational costs, greater flexibility, stronger corporate branding and enhanced cross‐functional communication. Despite the tens of millions of dollars spent to acquire and develop them, little research exists that has systematically tested the validity of the benefits attributed to a corporate campus. This paper reports on an initial set of case studies examining one potential benefit of a corporate campus: the nature and extent of comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 7 publications
0
29
0
Order By: Relevance
“…In recognition of their fluid needs, many organizations have established semi-structured settings to mediate the dynamic flow of interactions among relevant members. For example, company towns (Agrawal, Cockburn, and Rosell, 2010), headquarters (Kleinbaum and Stuart, 2013), or a corporate campus (Becker, Sims, and Schoss, 2003) allow for the collocation of key business organizational members. At a more micro-level, office layouts (Allen, 1977;Liu, 2013;Oldham and Brass, 1979), lunchrooms (Sommer, 1959), or even the placement of a restroom within a building (Pfeffer, 1992) is often sufficient to induce focused settings for the organic exchange of information (Feld, 1981).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…In recognition of their fluid needs, many organizations have established semi-structured settings to mediate the dynamic flow of interactions among relevant members. For example, company towns (Agrawal, Cockburn, and Rosell, 2010), headquarters (Kleinbaum and Stuart, 2013), or a corporate campus (Becker, Sims, and Schoss, 2003) allow for the collocation of key business organizational members. At a more micro-level, office layouts (Allen, 1977;Liu, 2013;Oldham and Brass, 1979), lunchrooms (Sommer, 1959), or even the placement of a restroom within a building (Pfeffer, 1992) is often sufficient to induce focused settings for the organic exchange of information (Feld, 1981).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…The sense of belonging is closely linked to corporate culture and identity, for which the facilities also bear meaning. Becker et al (2003) submits that the physical facilities on a campus are representative of the respective company culture, and that the employees appreciate a strong architectural branding. This resonates with Airo (2013) who found that, due to their academic identity, academics felt their workplace should reflect the academic tradition.…”
Section: Literaturementioning
confidence: 99%
“…), 2) shared facilities (e.g Green & Lazarus 1988),. and 3) sense of belonging (e.g Becker et al 2003)…”
mentioning
confidence: 99%
“…There are indeed many means of information delivery available, more numerous and diverse than those available to marketing communication managers, who usually resort to packaging and some sort of mass media advertising to inform and persuade consumers (King, 1991). personal online diary) (Leonard, 2003), and corporate campuses (Becker, Sims and Schoss, 2003). personal online diary) (Leonard, 2003), and corporate campuses (Becker, Sims and Schoss, 2003).…”
Section: Statement Of the Problemmentioning
confidence: 99%